Enigmatic Surface Ruptures at Cape Rytyi and Surroundings, Baikal Rift, Siberia: Seismic Hazard Implication - Oksana V. Lunina; Ivan A. Denisenko; Anton A. Gladkov; Carlos Braga (Quaternary, 2023)
The geomorphic expression of active faulting and distinction of paleoseismic events in areas that are rapidly obscured by erosion/sedimentation still remains a considerable scientific problem. The present article discusses the revealing of surface faulting ruptures and their parameters to identify capable faults without trenching and to estimate the magnitude of earthquakes. The case study was at Cape Rytyi, located in Baikal-Lena Nature Reserve on the northwestern shore of Lake Baikal. Based on unmanned aerial photography, GPR, and structural observations, we mapped and investigated the relation between geomorphological forms and ruptures. The obtained results show that past landslides and paleoruptures at Cape Rytyi and its surroundings are associated with at least two earthquakes. The Mw of the earlier event was 7.3 (Ms = 7.4); the Mw of the later one was 7.1 (Ms = 7.3). The paleoruptures in the distal part of the delta of the Rita River and on the southeastern slope of the Baikal Ridge were included in the seismogenic rupture zone, which traces some 37 km along the Kocherikovsky fault. The approximate intervals in which earthquakes occurred are 12–5 ka and 4–0.3 ka, respectively. The applied analysis methods can be useful for paleoseismology and assessing seismic hazards in similar regions elsewhere.